Implementation Of E-Government In Population Administration Services Through The SAHAJA (One Day) Online Application At The Population And Civil Registration Office Of Kediri Regency In 2024-2025 - Fathia Rahma Sholikhah (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This research is motivated by the implementation of E-Government as part of the government's efforts to improve the quality of public services through the use of information and communication technology. One such implementation has been carried out by the Kediri Regency Population and Civil Registration Office through the Sahaja (One Day) Online application, a digital-based population administration service. This study aims to describe and analyse the implementation of E-Government in population administration service through the Sahaja Online application at the Population and Civil Registration Office of Kediri Regency for the period 2024-2025. The study employs a qualitative research method with a descriptive approach. Data collection techniques included interviews, observation, and documentation. The analysis of the study utilized the theory of the success factors in E-Government development from the Harvard JFK School of Government, cited by Indrajit (2006), which encompasses support, capacity, and value. The research findings indicate that the implementation of E-Government through the Sahaja Online application is underway, but has not yet been optimised. In terms of support, there is government backing, government commitment, and inter-agency cooperation. However, there are inconsistencies in support for human resources relating to bureaucracy and finance, and public awareness campaigns have not been carried out in a uniform and sustainable manner. In terms of capacity, the availability of information technology infrastructure is considered adequate; however, there are still limitations regarding the availability of financial resources and competent human resources. In terms of value, the Sahaja Online application provides benefits in the form of convenience, time efficiency, cost savings, and improved quality of civil registration service for the public.